2010
DOI: 10.3109/00016340903295618
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and histidine‐rich glycoprotein in early‐onset preeclampsia

Abstract: HRG and fibrinogen might be involved in the hypercoagulability and the angiogenic imbalance seen in early-onset preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…In three studies, an increase was reported. 16,20,32 In contrast, two studies by Schjetlein et al 33,34 reported a decreased plasma level of fibrinogen, similarly to what we found in our study using first trimester PE serum. The conflicting findings may be attributed to other factors that also regulate fibrinogen levels but differ between the various studies.…”
Section: Discussionsupporting
confidence: 86%
“…In three studies, an increase was reported. 16,20,32 In contrast, two studies by Schjetlein et al 33,34 reported a decreased plasma level of fibrinogen, similarly to what we found in our study using first trimester PE serum. The conflicting findings may be attributed to other factors that also regulate fibrinogen levels but differ between the various studies.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously shown that HRG might be of importance in early pregnancy and this is supported by our prior results indicating an association between the presence of HRG in placenta and risk of preeclampsia during pregnancy [15], as well as between the HRG C633T SNP and pregnancy outcome among patients undergoing in vitro fertilization [18]. …”
Section: Discussionsupporting
confidence: 73%
“…We have previously shown that HRG exists in the reproductive system as well as in the embryo [14] and it is involved in the hypercoagulability and the angiogenic imbalance seen in early onset preeclampsia [15]. HRG has been reported to exist as at least ten naturally occurring single nucleotide polymorphisms (SNPs) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In preeclampsia, the function of the placental microvasculature is compromised and displays increased clot formation and activation of platelets. In a recent study, placentas from preeclamptic women were analyzed by immunohistochemistry with the aim to find prognostic markers (33). Interestingly, the placenta vasculature was positively stained by the antibody 0119 (used in our study), which is directed against the His/Pro-rich domain of HRG.…”
Section: Discussionmentioning
confidence: 99%